VD_FINDINFO Pron / 2012 / 90 vom 26. April 2012 - VD Tribunal cantonal (2012)
DÉCISION SUR FRAIS, TRANSACTION JUDICIAIRE | 105 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)